Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Berinvestasi Di Pasar Modal : Studi Pada Mahasiswa Fakultas Ekonomika Dan Bisnis Universitas Negeri Surabaya - Siti Mulyani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Investment is important in helping to increase the growth and development of a country. The total ratio of investors in Indonesia in 2022 is 2.2%, this ratio is still lagging behind when compared to other countries. Students are in the spotlight for the Indonesia Stock Exchange to become young investors in the capital market. The Indonesia Stock Exchange (IDX) has done several things to increase investment interest in universities by establishing several collaborations and organizing programs such as opening an Investment Gallery. This study aims to determine the effect of investment knowledge, investment benefits, investment motivation, minimum investment capital and investment return on investment interest in the capital market. The results of this study are that simultaneously investment knowledge, investment benefits, investment motivation, investment return and minimum capital have a positive effect on investment interest. Partially, investment knowledge, investment benefits, investment return and minimum capital have a positive effect on investment interest, while the investment motivation variable has no effect on investment interest. The ability of these 5 variables to influence investment interest is shown in the adjusted R square value of 53% and the rest can be influenced by other variables outside of this study